2005
DOI: 10.1177/1043454204270263
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Refusal of Medical Treatment for Cultural or Religious Beliefs: An Ethnographic Study of Health Care Professionals’ Experiences

Abstract: Pediatric nurses working in acute care settings serving religious and culturally diverse families may encounter parents whose beliefs influence treatment decisions. Previous literature describes how these complex situations lead to emotional distress and strained relationships between health care provider and family members. An ethnographic study was conducted to investigate the impact of parental treatment refusal on the bedside interactions between pediatric nurses and parents. Twenty in-depth interviews wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 5 publications
0
8
0
2
Order By: Relevance
“…A study from a paediatric ward in California on parents' refusal of medical treatment due to cultural or religious beliefs revealed that these complex situations led to emotional distress in the interaction between health care providers and family members. 37 In Malawi there is no external factor such as a law stating that it is unacceptable for a parent to deny a child life-saving treatment. Muula 15 claims that it is a challenge for the health authorities and Nurses' Associations of Malawi to be more active in initiating the discussion about whether such laws should be introduced.…”
Section: Discussionmentioning
confidence: 99%
“…A study from a paediatric ward in California on parents' refusal of medical treatment due to cultural or religious beliefs revealed that these complex situations led to emotional distress in the interaction between health care providers and family members. 37 In Malawi there is no external factor such as a law stating that it is unacceptable for a parent to deny a child life-saving treatment. Muula 15 claims that it is a challenge for the health authorities and Nurses' Associations of Malawi to be more active in initiating the discussion about whether such laws should be introduced.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of parents refusing to consent to medical procedures or treatment for their children in a number of pediatric clinical scenarios is well documented [5860], as are the numerous barriers to informed consent for complex genetic syndromes. Beneficence-based obligations support mandatory newborn screening for RET proto-oncogene mutations.…”
Section: Pediatric Ethics Guidelinesmentioning
confidence: 99%
“…Multicultural interaction in health care between clients and caregivers has been described as challenging and problematic worldwide [1]. These challenges were also found in the Swedish Primary Child Health Care services (PCHC services) [2-4].…”
Section: Introductionmentioning
confidence: 99%